Plant trait-based approaches to improve nitrogen cycling in agroecosystems - Abalos, Diego; van Groenigen, Jan Willem; Philippot, Laurent; Lubbers, Ingrid M.; De Deyn, Gerlinde B. (The Journal of applied ecology, 2019)
Intensive agriculture is dominated by monocultures of high‐yielding plants that receive large applications of nitrogen (N) fertilizers to boost plant productivity. However, these systems have low N use efficiency (NUE) as fertilized plants generally take up less than half of the N applied. A large fraction of the remainder N is susceptible to be lost from the agroecosystem generating a cascade of environmental and socio‐economic problems. Climate change and projected global increases in fertilizer use pose further risks to N losses and yield stability. We review and translate concepts from ecology in natural systems to demonstrate that NUE in intensive agroecosystems can be strongly increased by fine‐tuning the traits of the plant communities to the levels of N fertilization intensity. We present key plant traits of importance for N‐cycling (architectural, morphological and physiological traits, as well as symbiotic associations and exudation patterns); discuss ecological (with soil fauna and N‐cycling microbial communities) and agronomic interactions of this approach; propose interdisciplinary methodologies for future research ranging from pot to global scales; and highlight possible solutions leading to an optimal balance between N fertilizer use and productivity. Synthesis and applications. By showing the strong links between plant traits and nitrogen (N) cycling, our work opens possibilities to test ecologically informed hypotheses across gradients of soil fertility and N fertilizer management intensity, setting a research agenda for the coming years. Accordingly, the choice of plant species based on their functional traits will play a central role for the development of modern and productive agroecosystems that retain and use N more efficiently. By showing the strong links between plant traits and nitrogen (N) cycling, our work opens possibilities to test ecologically informed hypotheses across gradients of soil fertility and N fertilizer management intensity, setting a research agenda for the coming years. Accordingly, the choice of plant species based on their functional traits will play a central role for the development of modern and productive agroecosystems that retain and use N more efficiently.